"Optimizing the Role of Parents in Monitoring Children's Assignments and Attendance through the Electronic Parents Control Program to Develop Quality Students" - Utami, Wahyu (Journal Social Sciences and Humanioran Review, 2024)
The responsibility of educating students is not only carried out by teachers at school but is a shared responsibility that includes parents. However, in practice, it seems that teaching and educating is solely the responsibility of teachers. Not only is there a lack of involvement at school, but only a small percentage of parents are actively involved in checking their children's assignments, whether at the elementary, junior high, or especially high school levels. As a result, many parents only become aware of their children's academic performance when they receive their report cards at school. This situation cannot be entirely blamed on the parents, as there has not yet been a widespread government policy regarding the involvement of parents in collaboration with teachers in the educational process, including monitoring their children's assignments and attendance. The method used in this study is classroom action research, aiming to optimize the role of parents so that students become more disciplined in submitting assignments and attending school. The sample in this research consists of students, parents, teachers, and the principal. Three research instruments were used: observation, interviews, and questionnaires. Interviews were conducted with students, teachers, and the principal, while questionnaires were given to parents to gauge their perceptions regarding the level of satisfaction, usefulness, and sustainability of the EPC program. The data was processed using descriptive statistical analysis. The results of this study show that the role of parents in monitoring their children's assignments and attendance through EPC is highly effective. In Class XII A, the discipline in submitting assignments increased from 82.8% to 97%, and attendance from 80% to 100%. In Class XII F, discipline in submitting assignments rose from 57% to 97%, and attendance from 80% to 100%. Additionally, the evaluation of the usefulness of EPC showed that 18 out of 32 respondents strongly agreed, while 14 others agreed that the EPC program should be continued for all subjects at SMA N 1 Bungo. Parents suggested that EPC be implemented in all subjects, and both the principal and teachers recommended applying this program to all subjects.